(untitled) (Palimpsesto, 2023)
This essay aims to analyze the feasibility of implementing an intelligent scientific ecosystem in Venezuela to overcome the current crisis in the country. The methodology consists of a rigorous and critical analysis of relevant literature, which addresses aspects such as investment in research and development, the creation of institutions that support innovation, and the development of appropriate regulations to promote science and technology in Venezuela. In conclusion, it is deduced that the implementation of an intelligent scientific ecosystem can promote the advancement of research in the country, stimulating invention and competitiveness in the global economy.